¿Por qué cambian los precios? - Wiener Fresco, Hugo Carlos (2023)
In a previous Academic Note, I dealt with the key indicator of the economy, the measure of growth that is the Gross Domestic Product. There I warned that the presentation was incomplete because it was necessary to deal with the effect of price variations (inflation) in year-on-year comparisons, and to isolate the effect of real growth from nominal growth, which is the mirage that money creates. This task is addressed in this installment. It explains how money is created in today's world, the role of banks, how the current world monetary order was formed. It concludes with a review of the indicators used to measure the variation in GDP prices as well as consumer goods and services.